Insights into the pathophysiology of Alzheimers disease and potential therapeutic targets: a current perspective - Rajah Kumaran, Kesevan; Yunusa, Suleiman; Perimal, Enoch; Wahab, Habibah; Müller, Christian P.; Hassan, Zurina (IOS Press, 2023)
The aging population increases steadily because of a healthy lifestyle and medical advancements in healthcare. However, Alzheimer’s disease (AD) is becoming more common and problematic among older adults. AD-related cases show an increasing trend annually, and the younger age population may also be at risk of developing this disorder. AD constitutes a primary form of dementia, an irreversible and progressive brain disorder that steadily damages cognitive functions and the ability to perform daily tasks. Later in life, AD leads to death as a result of the degeneration of specific brain areas. Currently, the cause of AD is poorly understood, and there is no safe and effective therapeutic agent to cure or slow down its progression. The condition is entirely preventable, and no study has yet demonstrated encouraging findings in terms of treatment. Identifying this disease’s pathophysiology can help researchers develop safe and efficient therapeutic strategies to treat this ailment. This review outlines and discusses the pathophysiology that resulted in the development of AD including amyloid-β plaques, tau neurofibrillary tangles, neuroinflammation, oxidative stress, cholinergic dysfunction, glutamate excitotoxicity, and changes in neurotrophins levels based on the literature search from Scopus, PubMed, ScienceDirect, and Google Scholar. Potential therapeutic strategies are discussed to provide more insights into AD mechanisms by developing some possible pharmacological agents for its treatment.